2021
DOI: 10.3390/ijms22041923
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Marine Agarose Biomaterials for Tissue Engineering Applications

Abstract: Five agarose types (D1LE, D2LE, LM, MS8 and D5) were evaluated in tissue engineering and compared for the first time using an array of analysis methods. Acellular and cellular constructs were generated from 0.3–3%, and their biomechanical properties, in vivo biocompatibility (as determined by LIVE/DEAD, WST-1 and DNA release, with n = 6 per sample) and in vivo biocompatibility (by hematological and biochemical analyses and histology, with n = 4 animals per agarose type) were analyzed. Results revealed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 53 publications
6
16
0
Order By: Relevance
“…Although FA biomaterial showed promising results in tissue engineering of the cornea, skin, nerve, tendon, sclera and oral mucosa, the biocompatibility and biomechanical properties of this biomaterial still need to be improved [ 27 , 28 , 29 , 30 , 31 , 32 ]. In this regard, we recently demonstrated that different types of marine agaroses could have specific biological and biomechanical properties, suggesting that not all currently available marine agaroses polysaccharides show the same behavior both in vitro and in vivo [ 23 ]. In the present work, we evaluated several agaroses at increasing concentrations to determine their putative usefulness for the generation of human bioartificial tissues by tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although FA biomaterial showed promising results in tissue engineering of the cornea, skin, nerve, tendon, sclera and oral mucosa, the biocompatibility and biomechanical properties of this biomaterial still need to be improved [ 27 , 28 , 29 , 30 , 31 , 32 ]. In this regard, we recently demonstrated that different types of marine agaroses could have specific biological and biomechanical properties, suggesting that not all currently available marine agaroses polysaccharides show the same behavior both in vitro and in vivo [ 23 ]. In the present work, we evaluated several agaroses at increasing concentrations to determine their putative usefulness for the generation of human bioartificial tissues by tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
“…Marine polysaccharides are other natural biomaterials that has been used in tissue engineering of different tissues and organs [ 20 ]. The inherent natural properties of these marine products such as biodegradability and biocompatibility, make agarose a perfect product to be used a scaffold in tissue engineering [ 21 , 22 , 23 ]. Agarose is a natural polysaccharide that exhibits controlled self-gelling properties, water solubility, and high biocompatibility, and it has been demonstrated that this material could enhance cell proliferation and activity [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell proliferation was then analyzed with the WST-1 colorimetric assay (Cell proliferation reagent WST-1, Sigma/Aldrich Merck) as previously reported 28 , 29 . Briefly, water-soluble tetrazolium salt was added to the culture medium of each study group (HSEC cultured with the different types and concentrations of secretome at different time points), and cells were incubated in this mixture for 4 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%